Gema Cow-Pu: Development of Mathematical Crossword Puzzle Learning Media on Students' Critical Thinking Ability - Darmayanti, Rani (CV. Bimbingan Belajar Assyfa, 2023)
Critical personality is a skill that must be possessed in order to survive in the global competition of 21st century society. Given that critical thinking education is an important part of human life, innovations must be carried out to foster students' critical thinking. One of the studies he conducted was the innovation of crossword learning media (GEMA COW-PU). In this study, the development of learning media for mathematical crossword puzzles (Gema Cow-Pu) was carried out on Geometry material at YALC Pasuruan Middle School and tested the learning media on students' critical thinking skills. This is intended to determine its validity and practicality. The specialty of this research is research and development based on the Borg n Gall development model. The research subjects were ten students of class VIII. The instruments used were validation sheets, teacher and student response questionnaires, and student learning outcomes tests. The results showed that the relevance score of Gema Cow-Pu learning media with students' critical thinking skills was in the very valid category with an average score of 89.75 percent, and Practical with a percentage of 95.3%. This shows that the Gema Cow-Pu learning media meets valid and practical criteria so that it can help students' critical thinking skills in learning